(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2025)
Anthropogenic activities such as crop production in the watershed of Kiri Reservoir give rise to the use of fertilizers and pesticides to increase yield and enhance quality produce. However, these xenobiotics enter into the aquatic environment via runoff and are sources of heavy metals that cause harmful effects on nontarget organisms. Species-specific bioaccumulation of heavy metals in some commercial fish (Oreochromis niloticus, Synodontis clarias, and Clarias gariepinus) from Kiri Reservoir, Nigeria, were assessed on a temporal basis from August, 2023 through January 2024. An Atomic Absorption Spectrophotometer was used to identify and determine the bioaccumulation of six heavy metals; Cadmium, Nickel, Lead, Arsenic, Chromium, and Zinc in the fish species. Chromium recorded the highest mean bioaccumulation values in the order of 2.360 ± 0.016 µg/g, 2.060 ± 0.008 µg/g, and 2.043 ± 0.013 µg/g for C. gariepinus, S. clarias and O. niloticus respectively in October. Cadmium was the least with the following decreasing mean bioaccumulation of 0.080 ± 0.000µg/g in December, 0.038 ± 0.000 µg/g, 0.007 ± 0.000 µg/g in January for S. clarias, C. gariepinus and O. niloticus respectively. There were significant differences (p < 0.05) in the bioaccumulation of heavy metals among the three fish species and on a temporal basis. S. clarias recorded the highest level followed by C. gariepinus and then O. niloticus. This study concludes that the bioaccumulation of heavy metals in the fish species was influenced by the species type and local weather conditions beyond their chemical characterizations.